Lung dose measurement from indoor 222Rn and 220Rn in dwellings of Fatehgarh district of Punjab, India. (December 2020) - Kaur, Rupinderjeet; Shikha, Deep; Gupta, Ruchie; Singh, Tejinder; Kumar, Amit; Singh, Supreet Pal; Mehta, Vimal
Abstract: In order to study the health risk factors caused by indoor radon and thoron gases, environmental testing of these gasses has been carried out in various dwellings in the Fatehgarh district of Punjab. The average concentration of indoor 222 Rn (CR ) and indoor 220 Rn (CT ) is 59.8±15.9 Bq/m 3 and 70.6±22.4 Bq/m 3 . The equivalent dose rate for lung (H) ranges from 33.54 to 82.60 nSv with mean dose of 47.85±12.73 nSv. The Effective dose rate to lungs (DLung ) due to radon emitted alpha particles and progenies ranges from 1.68 to 4.13 nGy h -1 with mean of 2.39±0.63 nGy h -1 . The effective dose rates trachea-bronchial (DT-B ) and pulmonary + pulmonary lymph (DP+PI ) ranges from 2.01 to 4.96 nSv with average value of 2.86±0.63 nSv. The rate of lung dose DRL owing to radon varies from 4.03 to 9.91 nSv with average value of 5.74±1.52 nSv. The average of the 222 Rn and 220 Rn inhalation dose in the study region is not as much of the 222 Rn and 220 Rn overall average inhalation dose worldwide.